Genome-Wide Analysis of Simple Sequence Repeats and Efficient Development of Polymorphic SSR Markers Based on Whole Genome Re-Sequencing of Multiple Isolates of the Wheat Stripe Rust Fungus - Luo, Huaiyong; Wang, Xiaojie; Zhan, Gangming; Wei, Guorong; Zhou, Xinli; Zhao, Jing; Huang, Lili; Kang, Zhensheng (PLOS ONE, 2015)
The biotrophic parasitic fungus Puccinia striiformis f. sp. tritici (Pst) causes stripe rust, a devastating disease of wheat, endangering global food security. Because the Pst population is highly dynamic, it is difficult to develop wheat cultivars with durable and highly effective resistance. Simple sequence repeats (SSRs) are widely used as molecular markers in genetic studies to determine population structure in many organisms. However, only a small number of SSR markers have been developed for Pst. In this study, a total of 4,792 SSR loci were identified using the whole genome sequences of six isolates from different regions of the world, with a marker density of one SSR per 22.95 kb. The majority of the SSRs were di- and tri-nucleotide repeats. A database containing 1,113 SSR markers were established. Through in silico comparison, the previously reported SSR markers were found mainly in exons, whereas the SSR markers in the database were mostly in intergenic regions. Furthermore, 105 polymorphic SSR markers were confirmed in silico by their identical positions and nucleotide variations with INDELs identified among the six isolates. When 104 in silico polymorphic SSR markers were used to genotype 21 Pst isolates, 84 produced the target bands, and 82 of them were polymorphic and revealed the genetic relationships among the isolates. The results show that whole genome re-sequencing of multiple isolates provides an ideal resource for developing SSR markers, and the newly developed SSR markers are useful for genetic and population studies of the wheat stripe rust fungus.